Legal Review of Compensation for Revocation of Land Rights for the Purpose of Toll Road Construction - Leyla Vani Panjaitan; Janpatar Simamora; Jinner Sidauruk (Journal of Legal and Cultural Analytics, 2025)
Land issues in Indonesia are an important issue that affects people’s lives, especially in the context of infrastrcture development. This study aims to analyze the form of compensation for the recovation of land rights for toll read construction and legal remedies that can be taken by land owners if compensation is not paid. The research method used is normative juridical with a qualitative approach, referring to the applicable laws and regulations, especially Lae No. 2 of 2012 and UUPA No. 5 of 1960. The results of the study show that the land acqusition proscess involves the stages of invertaarization, value determination, deliberation, compensation, and release of land rights. Compensation can be in the form of money, replacement land, resettlement, or shares. In the event of disagreement, the landowner has the right to file an objection to the District  Court and proceed to the Supreme Court if dissatisfied with the decision. This study emphaisizes the importance of legal protection for landowner in the process of land acquisition for the public interest.